Studies of a Mechanically Pumped Two-Phase Loop with a Pressure-Controlled Accumulator Under Pulsed Evaporator Heat Loads - Nicholas Truster; Jamie S. Ervin; Abdeel Roman; Jeff Monfort (Energies)
As avionics become more power dense, electronic device cooling has become a significant barrier to aircraft integration. A mechanically pumped two-phase loop (MPTL) is a thermal subsystem that enables near isothermal evaporator operation, which is desirable for electronics cooling. The goal of this study was to integrate an MPTL with a pressure-controlled accumulator and model a predictive control technique to demonstrate improvements for transient, isothermal evaporator operation for MPTLs under pulsed evaporator heat loads. The model predictive controller enables active control of MPTL compressible volume, which has not been demonstrated for pulsed evaporator heat loads. Experimental data were collected to validate a representative numerical model. A pressure-controlled accumulator was added to an MPTL to experimentally characterize the system thermodynamic response for three pulsed evaporator heat loads. Two statistical methods were used to assess the numerical model agreement with the experimental results. Under pulsed evaporator heat loads, the mean percent error agreed within 3.45% and the mean average percent error agreed within 0.74% for the three pulsed evaporator heat loads. Finally, a traditional proportional–integral (PI) controller and an advanced model predictive controller were developed and integrated into the validated numerical model. Both control methods were evaluated for an expanded set of evaporator heat load profiles to analyze transient behavior. For evaporator heat profiles with high heat transfer rates, the model predictive controller can maintain a target ±2 K refrigerant temperature at the evaporator exit throughout the evaporator heat load duration, whereas the PI-controlled MPTL cannot. Through this work, active control of a pressure-controlled accumulator within an MPTL is shown to improve refrigerant isothermal (±2 K) operation when compared to a traditional control technique.